Addressing gender based violence and psychosocial support among South Sudanese refugee settlements in northern Uganda. Issue 1 (March 2017) - Mogga, Rose
Abstract : This personal reflection describes how the nongovernmental organisation, TPO Uganda, tried to expand an existing programme providing psychosocial support to survivors of sexual gender based violence in refugee camps in Adjumani District to Bidibidi in Yumbe District, Uganda with an enormous group of new refugees from South Sudan. It describes the kind of (sexual) gender based violence the refugee girls and women experience, how staff try to find these women and provide support through using cognitive behavioural treatment therapy for trauma intervention. The author gives voice to the women who went through this intervention and shows the challenges staff experience in supporting new resettlements of more than 200, 000 people since opening in August 2016.